Serpong Ship Board Performance Influenced by Training and Work Placement Case Study PT. Bumi International Tanker - Sukur Yanus Zai; Jones Zenas Rante; Ratnawati Prayogi (MultiTech Publisher, 2023)
The performance of the ship's crew is influenced by the motivation of each individual, level of education, training received and the progress of company management. In general, ship crews are given training and become trained so that they have high productivity. From the descriptions above, it can be concluded that the existence of training for ship crew is something that needs to be considered by the company in an effort to improve crew performance which directly changes the company's progress. The main problem in this study is how much influence the training and placement of ship crew work either partially or simultaneously on the performance of MT ship crews. Jayne 1. The method used in this study is an associative research method. The purpose of associative research is a research that seeks the relationship between one variable and another variable. This research was conducted on MT Ship Crew. Jayne 1 At PT. Earth International Tankers. The research and observations were carried out from March 2022 to June 2022. The sample technique used in this study was the census method, and the data analysis technique used was multiple linear regression analysis using the SPSS version 20 software. Based on the analysis conducted it can be concluded that training and work placements significantly either partially individually or jointly affect the performance of the crew of the MT ship. Jane 1